Study of anisotropy through microscopy, internal friction and electrical resistivity measurements of Ti-6Al-4V samples fabricated by selective laser melting. Issue 6 (7th January 2022) - Nespoli, Adelaide; Bennato, Nicola; Villa, Elena; Passaretti, Francesca
Abstract : Purpose: This paper aims to investigate the microstructural anisotropy of Ti-6Al-4V samples fabricated by selective laser melting. Design/methodology/approach: Specimens are fabricated through a Renishaw AM400 selective laser melting machine. Three microstructures (as-built, 850°C annealed and 1, 050°C annealed) and two building orientations, parallel (PA) and perpendicular (PE) to the building platform, are considered. Starting from in-depth microscopic observations and comprehensive electron backscattered diffraction imaging, the study addresses non-conventional techniques such as internal friction and electrical resistivity measurements to assess the anisotropy of the fabricated parts. Findings: Microscope observations highlight a fine texture with columnar grains parallel to the building direction in the as-built and 850°C annealed samples. Besides, coarse grains characterized the 1, 050°C annealed specimens. Internal friction measurements pointed out the presence of internal stress while storage modulus analyses appear sensitive to texture. Electrical resistivity is resulted to be dependent on grain orientation. Originality/value: The work uses some novel characterization techniques to study the anisotropy and internal stresses of Ti-6Al-4V samples processed by selective laser melting. Mechanical spectroscopy results suitable in this kind of study, as it mimics the operating conditions of the material.